A Theory of Wage Adjustment under Loss Aversion - Steffen Ahrens; Inske Pirschel; Dennis J. Snower (Institute for the Study of Labor (IZA), 2014)
We present a new theory of wage adjustment, based on worker loss aversion. In line with prospect theory, the workers' perceived utility losses from wage decreases are weighted more heavily than the perceived utility gains from wage increases of equal magnitude. Wage changes are evaluated relative to an endogenous reference wage, which depends on the workers' rational wage expectations from the recent past. By implication, employment responses are more elastic for wage decreases than for wage increases and thus firms face an upward-sloping labor supply curve that is convexly kinked at the workers' reference price. Firms adjust wages flexibly in response to variations in labor demand. The resulting theory of wage adjustment is starkly at variance with past theories. In line with the empirical evidence, we find that (1) wages are completely rigid in response to small labor demand shocks, (2) wages are downward rigid but upward flexible for medium sized labor demand shocks, and (3) wages are relatively downward sluggish for large shocks.
Keywords: D03; D21; E24; 330; downward wage sluggishness; loss aversion